Organising a medical camp in a community: are there lessons to be learned? - R., Ruban; Rai, S. Bina (International Journal Of Community Medicine And Public Health, 2019)
Part of curriculum requirements for year 3 medical students at AIMST University is to organise a medical camp at end of their community medicine posting. The purpose was two-fold: to orientate medical students towards health needs of the people at primary care level and to bring health awareness to communities that have less access to basic health care services. Annually, seven such camps are held. Our aim was to assess the lessons learned by medical students in this activity and we based our findings from a camp held on January 2018 in village PB. This is a descriptive review. Once the location is selected, the rest is by the medical students - format of camp, flow, type of services offered, medications, invitations, alternate programmes, consultations and referral with assistance from faculty. A stipend of RM 500.00 is provided to cover expenses. A post-mortem is held finally to review feedback, lessons learned and to compile a report. Total of 154 people registered at this camp. We involved the students with an aerobic session. We engaged the village leaders in the opening ceremony. We worked with the local health department to assist in the programmes. Lessons learned were planning, teamwork, empathy, self-efficacy, compromise, leadership quality and resourcefulness. Funding was insufficient, and we sourced through well-wishers and supportive local doctors. Medical camps benefit students, community and the institution the students are from. Community involvement and intersectoral collaboration is essential for best benefits.